26 Feasibility of therapeutic hypothermia in stemi: single UK heart attack centre experience. (24th April 2016) - Karamasis, Grigoris V; Islam, Shahed; MohdNazri, Shah; Al-Janabi, Firas; Watson, Noel; Gudde, Ellie; Gudde, Tom; Tang, Kare H; Kelly, Paul A; Davies, John R; Keeble, Thomas R
Abstract : Background: Primary PCI is the gold standard treatment for acute STEMI, but reperfusion injury limits its beneficial effect on infarct size (IS). In experimental studies, therapeutic hypothermia (HT) consistently reduces IS caused by reperfusion injury, but translation into clinical practice remains a challenge. The purpose of our study (part of COOL AMI EU study) was to assess the feasibility of integrating pre-reperfusion HT using an intravascular temperature management system (Thermogard XP, ZOLL, USA) into routine clinical practice without a significant delay in door-to-balloon (DTB) time. Methods: Patients with STEMI presenting within 6 h of symptoms onset and planned for PPCI were prospectively enrolled. TH was implemented by intravenous infusion (IV) of cold saline and a heat-exchange balloon catheter inserted via the right femoral vein. Oral buspirone and IV pethidine were used to control shivering. HT was continued for a total time of 3 h, followed by passive rewarming. Results: 18 patients were successfully recruited. The average age was 60.3 years and 94.4% were male. The DTB time was 40.6 min. There was an increase of 3.6 min compared with the mean DTB time of 37 min for patients who underwent PPCI and did not received HT. Mean temperature at reperfusion was 34.4 ° C. There were no adverse events related to the use of the heat-exchange catheter or the implementation of hypothermia. Conclusion: Hypothermia is feasible and safe in STEMI patients without significant delay in door-to-balloon time.